Prohibiting the Carrying of Concealed Deadly Weapons, Ordinance no. 84, in Charter and Ordinances of the City of Sacramento (1876) - (:unkn) unknown (My University, 1876)
Prohibited the concealed carry of a pistol, dirk, or other dangerous or deadly weapon without a license.
Keywords: CARRY - CONCEALED